A Decade of Global Skull Base Researchers: Gender Data from over 2,700 Abstract Authors in the Journal of Neurological Surgery Part B: Skull Base - Behmer Hansen, Rosemary T.; Behmer Hansen, Ryan A.; Gold, Justin L.; Blocher III, William A.; Palma, Samantha D.; Susman, Stephen J.; Batchu, Sai; Silva, Nicole A.; Richardson, Angela M. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objective The North American Skull Base Society (NASBS) annual conference brings together skull base researchers from surgical and nonsurgical fields. Our objective was to quantify the contributions of the authors by gender, who presented their work at NASBS and were subsequently published in the Journal of Neurological Surgery Part B: Skull Base.Methods Oral and poster abstracts presented at the NASBS annual meeting from January 1, 2011 to December 31, 2020 were extracted from the Journal of Neurological Surgery Part B: Skull Base. The genderize.io Web application programming interface was utilized to determine authorship gender. A minority of first and last authors had departmental affiliations listed; a subgroup analysis was performed of these authors.Results Female gender was assigned to 498 (17.8%) of the 2,798 first authors and 269 (9.7%) of the 2,762 last authors. Female authorship has consistently increased over the last decade. Representation was higher in otolaryngology (23.3% of first authors, 12.1% of last authors; p = 0.018) than neurosurgery (13.5% of first authors, 4.3% of last authors; p = 0.004). Female researchers were not less likely than their male counterparts to receive prestigious oral presentations. Of the 52 total countries represented, 20 (38.5%) had at least one female first author. Representation varied dramatically between countries.Conclusion The NASBS' efforts have undoubtedly contributed to these impressive strides toward gender parity. More work is needed to ensure that the best and the brightest, regardless of background, continue to contribute to skull base surgery research.
Keywords: skull base; otolaryngology; gender; authorship; abstract